A Comparative-Contrastive Analysis of Punctuation Use (and Spelling) in Serbian and English - Čorboloković, Saša S.; Gavranović, Valentina M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper investigates punctuation rules and their application in Serbian and English, focusing on the examples that comply with different normative solutions in the two languages. The main goal of the research is to compare and contrast the results obtained from a survey done by a group of seventh-grade primary school students. The paper aims to determine how well the respondents apply punctuation rules in Serbian and English, to examine whether there is interference in the application of rules, and to investigate to what extent the detected errors illustrate the tendency of spreading pseudo-norms that violate the orthography of both languages. The results show that the respondents use punctuation marks with more precision in Serbian than in English. The percentage of incorrect answers to each question and the types of errors indicate interference and the creation of hybrid forms that are incorrect in both languages, which represent the creation of pseudo-norms. Furthermore, the results show a greater influence of the application of the rules adopted in the Serbian language on the English language, which can be interpreted by the bigger number of Serbian classes and clearly stated topics within the syllabus of the Serbian language course.
Keywords: the English language; the Serbian language; spelling; punctuation marks; interference; pseudo-norm